2019
DOI: 10.1016/j.jconrel.2019.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-guided nanoparticles for glioblastoma targeting

Abstract: Tumor-selective drug conjugates can potentially improve the prognosis for patients affected by glioblastoma (GBM) -the most common and malignant type of brain cancer with no effective cure.Here we evaluated a novel tumor penetrating peptide that targets cell surface p32, LinTT1 (AKRGARSTA), as a GBM targeting ligand for systemically-administered nanoparticles. LinTT1-functionalization increased tumor homing of iron oxide nanoworms (NWs) across a panel of five GBM models ranging from infiltratively-disseminatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 58 publications
0
40
0
Order By: Relevance
“…Nanoparticle synthesis and functionalization. The iron oxide nanoworms (NWs) were prepared according to a published protocol by 8,26,27 . The aminated NWs were PEGylated using maleimide-5K-PEG-NH.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanoparticle synthesis and functionalization. The iron oxide nanoworms (NWs) were prepared according to a published protocol by 8,26,27 . The aminated NWs were PEGylated using maleimide-5K-PEG-NH.…”
Section: Methodsmentioning
confidence: 99%
“…Peptides were coupled to NWs through a thioether bond between the thiol group of a cysteine residue added to the N-terminus of the peptide. The concentration of the NWs was determined by measuring the absorbance of NWs at 400 nm with a NanoDrop 2000c spectrophotometer (Thermo Scientific) 8,27 . Silver nanoparticles (AgNPs) were synthesized and functionalized as described 28 , CF647-N-hydroxysuccinimide-dye (NHS-dye) was conjugated to the PEG terminal amine groups, and biotinylated peptides were coated on the NeutrAvidin (NA) on the surface of the AgNPs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the in vivo study showed that the targeting nano-delivery systems could accumulate within the tumor to a greater extent with remarkable decrease in the adverse effects of paclitaxel when compared with non-targeted nanosystems (Lei et al, 2019). Säälik et al (2019) investigated the effect of a novel penetrating peptide-guided nanoparticles that targets cell surface LinTT1, p32 for glioblastoma targeting. In this study, the coupling of LinTT1 to albumin-paclitaxel nano-delivery systems was achieved by sulfosuccinimidyl 4-(N-maleimidomethyl) cyclohexane-1-carboxylate as a linker.…”
Section: Other Functionalized Drug Delivery Systems For Targeted Thermentioning
confidence: 99%